The Effect of Competence and Lowballing on Audit Report Lag - Bari, Abdul; Nur Ikhwansyach, Radian; Kemalasari, Novawiguna; Badawi Saluy, Ahmad (DINASTI RESEARCH, 2025)
This study aims to determine the effect of Competence and Lowballing on Audit Report Lag. This study took a sample with the simple random sampling method. The population of this study are auditors who work at the Public Accounting Firm in Central Jakarta which is registered in the 2019 OJK Directory. This study uses primary data with Partial Least Square (PLS) analysis techniques. The results of this study indicate that the competency variable has no influence on the audit report lag, while the lowballing variable shows a significant effect on the audit report lag.